The child right of body protection in the international law A comparative study in Islamic shree - حوامدة, غالب (Journal of Legal Sciences, 2018)
The children are suffering from many kinds of tragedy acts such as killing and torture which arise from civil wars never be seen along the human history since decades.We still see millions of children suffering specially in the Arab world, Iraq, Syria, Libya, and Yemen. This study deals with kinds of protections which comes by international treaties and practiced by international organizations which helps in the protection through the military conflicts, and we compare this right in the Islamic shree, and how the states are comply with this right and how can they protect the children practically.At last we reach the conclusion and finally the recommendations.